Development Of Web-Based Science Learning in Living Things Interaction Materials to Improve ICT Literacy and Conceptual Understanding Skills - A. M. Azari; I. Wilujeng; S. Nurohman (Journal of Science Education Research, 2023)
The aims of this study are: 1) to produce feasible web-based science learning media, 2) to find out the effectiveness of the web-based science learning media for improving ICT literacy, 3) to reveal the effectiveness of the web-based science learning media for improving conceptual understanding, and 4) to determine the practicality of the web-based science learning media assisted by Google Sites on the interaction of living things material. This study was a research and development (RD) with the ADDIE model. Data collection instruments comprise feasibility sheets, students’ readability sheets, ICT literacy sheets, ICT literacy observation sheets, and pretest-posttest sheets of conceptual understanding. The research design used was one group pretest-posttest in class 7H of SMP Negeri 2 Adiwerna with 16 students. The data analysis techniques used were paired sample T-test, effect size, and n-gain. The results of this study were: 1) the web-based science learning media is feasible to be utilized in science learning, 2) web-based science learning media is effective in improving ICT literacy, 3) web-based science learning media is effective in improving conceptual understanding, and 4) web-based science learning media is practical for learning the interaction of living things material.